The Impact Of The Dimensions Of Electronic Advertising Via Social Networks On The Purchasing Behavior Of The Syrian Consumer (A Field Study On Tishreen University Students In Lattakia Governorate) - السكري أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to examine the effect of electronic advertising via social networks on the purchasing behavior of the Syrian consumer. To achieve this purpose, a field study was conducted that relied on directing a questionnaire to a random sample of Tishreen University students in Lattakia governorate from various faculties who use Facebook and Instagram, where (200) questionnaires were distributed to them, of which (188) were valid for statistical analysis. The study reached a set of results, the most important of which is the existence of a significant relationship between electronic advertising through social networks in its three dimensions (advertising credibility, advertising design, advertising content) on the one hand and the purchasing behavior of the Syrian consumer (clicking on the advertising, reading the advertising, recommending the advertising, ignorance the advertising, purchasing decision) on the other hand. The results also showed that the credibility of electronic advertising has the greatest influence on the purchasing behavior of the Syrian consumer, followed by the content of the advertising and then the design of the advertising. In addition to the above, the study concluded that the effect of electronic advertising via social networks on the purchasing behavior of the Syrian consumer is still weak, as this effect was limited to reading and recommending the advertising, while the majority neglected the advertising and avoided clicking on it and considered it unhelpful in making its purchasing decision.